Saccharomyces cerevisiae for lignocellulosic ethanol production: a look at key attributes and genome shuffling - Tsegaye, Kindu Nibret; Alemnew, Marew; Berhane, Nega (Frontiers in Bioengineering and Biotechnology, 2024)
These days, bioethanol research is looking at using non-edible plant materials, called lignocellulosic feedstocks, because they are cheap, plentiful, and renewable. However, these materials are complex and require pretreatment to release fermentable sugars. Saccharomyces cerevisiae, the industrial workhorse for bioethanol production, thrives in sugary environments and can handle high levels of ethanol. However, during lignocellulose fermentation, S. cerevisiae faces challenges like high sugar and ethanol concentrations, elevated temperatures, and even some toxic substances present in the pretreated feedstocks. Also, S. cerevisiae struggles to efficiently convert all the sugars (hexose and pentose) present in lignocellulosic hydrolysates. That's why scientists are exploring the natural variations within Saccharomyces strains and even figuring out ways to improve them. This review highlights why Saccharomyces cerevisiae remains a crucial player for large-scale bioethanol production from lignocellulose and discusses the potential of genome shuffling to create even more efficient yeast strains.